A Review on Time Travel: Fact or Fiction (International Journal of Innovative Research in Computer Science & Technology, 2022)
This article focuses on Einstein's theory of  relativity and Minkowski space-time, which combines  three dimensions of space and a fourth dimension of time.  It contrasts and examines the evolution of time travel in  science fiction and science. The wormhole hypothesis and  the Tipler cylinder are among the time travel hypotheses  investigated, as is the possibility of human time travel. This  research investigates time as a fourth dimension, as well as  curved space-time, both of which are often overlooked.  The paucity of information about time was one of my  major realizations throughout my studies, and I liked  investigating time as a social construct. Given how seldom  we ponder the effects of actions in our everyday lives, the  amount of hurdles to successful time travel was especially  apparent. Time travel was hampered by paradoxes, such as  the grandfather paradox, but I discovered techniques to  solve them throughout my studies. I also considered the  societal and economic implications of time travel, knowing  that the risks are numerous and could encourage corruption  in our cultures. Entropy
Keywords: Entropy; Paradox; Science; Time; Universe